On the coexistence of positive and negative externalities in the inter-powertrain relationships. (20th December 2020) - Mirzadeh Phirouzabadi, Amir; Blackmore, Karen; Savage, David; Juniper, James
Abstract: The green knowledge-based economy has complicated the dynamical knowledge interactions in the multi-technology sector of transportation that involves a constellation of interrelated powertrain technologies, including the internal combustion engine, hybrid and battery electric vehicles (ICEV, BEV, and HEV). Based on the biological ecology perspective and the technological innovation system (TIS) framework, we explore the dynamical inter-powertrain relationships in terms of knowledge diffusion over 1985–2016. We measure their knowledge diffusion by extracting patents and publications forward citations from the Scopus and Derwent databases, respectively. Quantifying by the Lotka-Volterra (L-V) equations, our results show that powertrains support and inhibit their knowledge diffusion growth by projecting positive and negative externalities, which are carried through the TIS co-dynamics. Our results reveal these externalities are manifested in a mix of biological relationship modes, such as symbiosis, parasitism, commensalism, and amensalism. We, therefore, challenge the assumed pure competition between ICEV and BEV or their predator-prey relationships with HEV by elaborating on the notions of 'creative destruction' and 'creative accumulation'. Our research contributes to the innovation systems literature by accommodating 'knowledge diffusion co-dynamics' as an extension to the TIS framework, making it more outward oriented. Moreover, the co-existence of positive and negative externalities builds up a multi cross-path interactions view that extends the conventional single-path view in the path dependency literature. Our research drives insightful knowledge for strategising and policy making in regard with investing in new disruptive technologies, sustaining the incumbent technology, or hybridising them as a transitionary (or stationary) solution towards sustainable mobility transition. Highlights: Multiple cross-path interactions exist in a multi-technology context. Powertrains interact in a mixed mode of symbiosis, commensalism, and amensalism and parasitism. Positive & negative externalities coexist in inter-powertrain relationships. Externalities are the mirror effect of powertrain's positive & negative internalities. Policies can drive a triple force of creation, destruction and accumulation.